STRATEGY FOR DEVELOPING THE BATURITI WATERFALL TOURISM OBJECT IN CATUR KARYA VILLAGE, BALINGGI DISTRICT, PARIGI MOUTONG DISTRICT - Tri Puspita Dewi (LPPM Universitas Tadulako, 2023)
Tourism is not only related to economic aspects, but also environmental, political, and socio-cultural aspects. The existence of Baturiti Waterfall has its attraction for visitors, it has clear water and is equipped with several showers that come from water sources. This research was carried out for two months, from September to November 2023. This research aimed to determine the Strategy for the Development of the Baturiti Waterfall Tourism Attraction in Catur Karya Village, Balinggi District, Parigi Moutong Regency. This research uses a survey method through interviews. Carrying out research and data collection uses observation techniques which are carried out by going directly to the field to find out the situation and conditions of the tourist attraction area. Interviews were conducted directly with the community using purposive sampling techniques (intentionally). The total number of respondents was 20 people, 3 community leaders, 15 tourists, and 2 tourism managers. The data analysis used is SWOT analysis (Strength, Wearability, Opportunity, and Treatment). SWOT is a structured planning method for evaluating the four elements of an organization, project, or business venture. The value of the X axis is ( 1.61 – 1.82 = (-0.21)) and the value of the Y axis is (1.77 – 1.27 = 0.5). So the strategy that must be applied in this situation is to support the Turn-around Strategy, namely taking advantage of all existing opportunities by carrying out active promotions through online media, improving accessibility and improving tourist attraction facilities/infrastructure, and exploring local culture so that it can be displayed as an attraction. routine.